VISUALISASI INDUSTRI KERAJINAN DI KABUPATEN JEPARA BERBASIS SISTEM INFORMASI GEOGRAFIS - ANTENG WIDODO (Indonesian Journal of Networking and Security (IJNS), 2019)
ABSTRACT An Economic Development of Regions sinificantly increase base on growth of industry in that area. Now a days we can see much industry small and large. Jepara is known as kota ukir, it not only has the industry craft of woodcarving only, but also has other industries such as is woven , craft sculpture, craft tile, craft bakery, craft Monel, local craft food, embroidery, handicrafts , and brass. The rapid development in the field of craft industries granted that It gives benefits on local economic development, but on the other side has given rise a problems to monitoring and control thing. Geographic Information Systems (GIS) Being Solution for that problems, visualize and monitor using digital maps, so that the Government does not require to visit Into the fields. each region can monitor the development of the handicraft industry. SIG develop using waterfall method that capable to be used for giving solution of the poblems.